2017
DOI: 10.1111/bjop.12252
|View full text |Cite
|
Sign up to set email alerts
|

To Brexit or not to Brexit: The roles of Islamophobia, conspiracist beliefs, and integrated threat in voting intentions for the United Kingdom European Union membership referendum

Abstract: We used an identities approach to examine voting intentions in the June 2016 UK referendum on membership of the European Union (EU). In April 2016, 303 British adults (58.7% women, age M = 34.73) indicated their voting intentions for the referendum and completed measures of identification with the national in‐group, perceived threat from Muslim immigrants, belief in Islamophobic conspiracy narratives, Islamophobia, general conspiracist beliefs, ambiguity tolerance, and belief in a clash of civilizations. Path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 88 publications
(142 reference statements)
8
64
1
1
Order By: Relevance
“…The present research supports this claim by showing that one year after the referendum, Leavers and Remainers are still split over the Brexit vote and their general political orientation. Consistent with the literature (Hobolt, ; Matti & Zhou, ; Meleady et al , ; Swami et al , ), we found that Leavers on average have a stronger ingroup identification and are more sceptical towards immigrants. In addition, Leavers valued security and tradition more and universalism less than Remainers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present research supports this claim by showing that one year after the referendum, Leavers and Remainers are still split over the Brexit vote and their general political orientation. Consistent with the literature (Hobolt, ; Matti & Zhou, ; Meleady et al , ; Swami et al , ), we found that Leavers on average have a stronger ingroup identification and are more sceptical towards immigrants. In addition, Leavers valued security and tradition more and universalism less than Remainers.…”
Section: Discussionsupporting
confidence: 92%
“…This research has mainly focused on the predictors of people’s voting decision. The findings revealed that the decision to vote ‘leave’ is associated with higher concerns about immigration and multiculturalism, British collective narcissism, Islamophobia, political conservatism, authoritarianism, distrust in the government, stronger British identity, social change insecurities, conspiracy beliefs, negative contact with EU immigrants, lower tolerance towards ambiguity, cognitive flexibility, agreeableness and openness personality traits, education, income, and increased age (Abrams & Travaglino, ; Becker, Fetzer, & Novy, ; Garretsen, Stoker, Soudis, Martin, & Rentfrow, ; Golec de Zavala, Guerra, & Simão, ; Harper & Hogue, ; Hobolt, ; Lee, Morris, & Kemeny, ; Matti & Zhou, ; Meleady, Seger, & Vermue, ; Swami, Barron, Weis, & Furnham, ; Zmigrod, Rentfrow, & Robbins, ). In short, these findings suggest that Leavers are more likely to express negative views of immigrants, to be higher in conservatism and distrust in politicians, and to be older and less educated.…”
Section: Introductionmentioning
confidence: 99%
“…It proved contentious among the public, the press and other politicians alike ("Do you think," n.d.-b;Durrheim et al, 2018), perhaps because of the perceived vulnerability of the group implicated. Nonetheless, this othering may be related to why Islamophobia, and a belief in Islamic conspiracy theories, has been linked to individual intentions to vote Leave (Swami et al, 2018). The…”
Section: Foundation 5: Sanctity/ Degradationmentioning
confidence: 99%
“…At one point this narrative became so ingrained in their messaging that the far-right British National Party said they were taking their territory by adopting a stance against the "Islamic colonisation" of Britain (Ford & Goodwin, 2014, p. 83). It also seems to have informed this part of the campaign, evoking nationalist identity politics to encourage a protectionist attitude towards an intergroup threat facilitated by EU expansion (Swami et al, 2018).…”
Section: Foundation 5: Sanctity/ Degradationmentioning
confidence: 99%
“…In the context of Brexit, the research focus has been on measuring the extent to which individual support for Brexit is associated with well-established psychological variables. Support for Brexit has been shown to be associated with prejudice in various ways: for instance, it has been found to be related to anti-immigration attitudes (Meleady, Seger, & Vermue, 2017), nationalistic attitudes, authoritarianism and cognitive inflexibility (Zmigrod, Rentfrow, & Robbins, 2018), and Islamophobia (Swami, Barron, Weis, & Furnham, 2018).…”
Section: Introductionmentioning
confidence: 99%